2020
DOI: 10.1155/2020/9502560
|View full text |Cite
|
Sign up to set email alerts
|

The YTH Domain Family of N6-Methyladenosine “Readers” in the Diagnosis and Prognosis of Colonic Adenocarcinoma

Abstract: To profile the landscape of methylation N6 adenosine (m6A) RNA regulators in colonic adenocarcinoma (COAD) and to explore potential diagnostic and prognostic biomarkers, we assessed the differential expression patterns of m6A RNA methylation regulators between 418 COAD patients and 41 controls based on profiling from The Cancer Genome Atlas (TCGA) database. We plotted the receiver operating characteristic (ROC) curves and calculated the area under the curve (AUC) values to estimate the discrimination ability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Previous study about CRC and m6A methylation focused on m6A regulators [ 32 ], one subtype of CRC, such as COAD [ 33 ], or the comparison of tumor and normal tissues [ 34 ]. In the study, we systematically analyzed RNA sequencing data of CRC (including COAD and READ) patients from TCGA and GEO database.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study about CRC and m6A methylation focused on m6A regulators [ 32 ], one subtype of CRC, such as COAD [ 33 ], or the comparison of tumor and normal tissues [ 34 ]. In the study, we systematically analyzed RNA sequencing data of CRC (including COAD and READ) patients from TCGA and GEO database.…”
Section: Discussionmentioning
confidence: 99%
“…According to the different CRC cohorts, ALKBH5 is low expression in CRC patients at mRNA and protein levels, playing a suppressor gene role in CRC. [61][62][63][64] Besides, the expression of ALKBH5 is significantly associated with age, stage, invasion and metastasis, overall survival and disease-free survival, which is also verified by experiments in vitro and in vivo. 64 However, some scholars argue that ALKBH5 is upregulated in CRC tissues and cells.…”
Section: Colorectal Cancermentioning
confidence: 55%
“…Studies have shown that YTHDC2 can specifically recognize and bind m6A through the YTH sequence, promote mRNA translation and affect mRNA stability (4). The YTHDC2 gene is essential for the maintenance of meiosis and the production of germ cells (23)(24)(25), and is involved in the occurrence and development of a variety of diseases, including autism, pancreatic cancer, colon adenocarcinoma, liver cancer, and lung adenocarcinoma (26)(27)(28)(29)(30). The HNRNPA2B1 gene was highly expressed in a variety of human cancers, such as prostate cancer (31), pancreatic cancer (32), and hepatocellular carcinoma (33).…”
Section: Discussionmentioning
confidence: 99%